Longitudinal Study of Brain Asymmetries in Autism and Developmental Delays Aged 2–5 Years. (15th April 2020) - Fu, Linyan; Wang, Yue; Fang, Hui; Xiao, Xiang; Xiao, Ting; Li, Yun; Li, Chunyan; Wu, Qiaorong; Chu, Kangkang; Xiao, Chaoyong; Ke, Xiaoyan
Highlights: A longitudinal study of brain asymmetry in toddlers with autism at 2–5 years old. The autism and developmental delay children showed a rightward asymmetry. The grey matter asymmetry is associated with the social ability in autism children. The white matter asymmetry is related to the repetitive behaviour in autism toddlers. Abstract: Some previous studies have demonstrated atypical brain lateralization in autism spectrum disorder (ASD). However, most of these reports have focused on language-related asymmetries in adults, and the developmental trajectory of hemispheric asymmetries in the important phase that occurs at 2–5 years of age remains unclear. Thus, we used structural magnetic resonance imaging and diffusion tensor imaging (DTI) in a longitudinal study of grey matter (GM) asymmetries across all cortical parcellation units (PUs) and white matter (WM) lateralization across the WM skeleton using voxel-based morphometry and tract-based spatial statistics (TBSS) in 34 toddlers with ASD and a matched group of 26 toddlers with developmental delay (DD) at 2–3 years old and with follow-up at 4–5 years of age. We found the total brain volume and fractional anisotropy (FA) of WM was higher in the ASD group than in the DD group at baseline and 2 years later. The ASD and DD groups showed a rightward asymmetry in a large number of cortical PUs and in the WM skeleton at both time points. GM lateralization was associated with the social and communicative disturbances observed in ASD at baseline, while WM asymmetry was significantly related to social disturbances and repetitive behaviours seen at 4–5 years of age. In conclusion, both ASD and DD toddlers had widespread rightward asymmetry, and the patterns of lateralization were similar across the groups. GM and WM showed asynchronous development of hemispheric asymmetries at 2–5 years of age, and this lateralization was associated with ASD symptoms.